Adiposity and Fat Distribution in relation to Inflammation and Oxidative Stress in a Relatively Lean Population of Chinese Women. Issue 4 (21st May 2013) - Wu, Sheng-Hui; Shu, Xiao-Ou; Chow, Wong-Ho; Xiang, Yong-Bing; Zhang, Xianglan; Cai, Qiuyin; Li, Hong-Lan; Milne, Ginger; Wen, Wanqing; Ji, Bu-Tian; Rothman, Nathaniel; Gao, Yu-Tang; et al.
Abstract : Objectives: This study evaluated associations of various anthropometric measures of adiposity with a panel of inflammatory and oxidative stress markers in a relatively lean population of Chinese women. Methods: This analysis included 1, 005 Chinese women aged 40–70 years. Plasma concentrations of inflammatory and oxidative stress markers were measured. Anthropometric measurements were taken by trained interviewers. Results: Body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR) were all positively and linearly associated with the inflammatory markers, CRP, TNF-α, soluble TNF-receptor 1 (sTNF-R1), and IL-6. A significant positive association of these measures of adiposity with the oxidative stress marker F2 -IsoP-M, a metabolite of F2 -IsoPs, but with not F2 -IsoPs was found. Differences in biomarkers between extreme quartiles of anthropometric measurements varied widely, ranging from 9.7% for sTNF-R1 to 162.0% for CRP. For each specific biomarker, various anthropometric measurements exhibited similar ability to explain variations in the biomarker, with the biggest partial r 2 (11%) observed for CRP. Conclusions: This study suggests that both general adiposity (measured by BMI) and central adiposity (measured by WC and WHtR) are positively and similarly associated with various markers of inflammation and oxidative stress in relatively lean Chinese women. The metabolite F2 -IsoP-M of F2 -IsoPs may be a better marker of in vivo oxidative stress than its parent compounds.